Pengaruh Model Cooperative Integrated Reading And Composition (Circ) Terhadap Hasil Belajar Mata Pelajaran Bahasa Indonesia Kelas III SDN 122381 Pematang Siantar - Intan Simangunsong; Theresia Monika Siahaan; Natalina Purba (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research aims to determine the effect of the Cooperative Integrated Reading (CIRC) Model to improve learning outcomes in class III Indonesian language subjects at SDN 122381 Pematang Siantar. The research design used was a quantitative approach with an experimental method in the form of a one group pretest posttest design without a comparison group. The population in the research study were all class III students at SDN 122381 Pematang Sianta. The sampling technique used is random sampling with two research variables, namely the dependent variable in the form of learning outcomes, and the independent variable, namely the CIRC Model. The data collection technique is the test technique. The results of hypothesis testing using the t test technique paired sample t test with the help of the SPSS Version 21 program, based on the calculation results that the significant value is 0.000<0.05 so that H0 is rejected and Ha is accepted or by comparing tcount>ttable with df=(n-1) namely the value of t = 22.103 > 2.064. So it can be concluded that there is an influence of using the Cooperative Integrated Reading (CIRC) Model to improve learning outcomes in class III Indonesian language subjects at SDN 122381 Pematang Siantar.